Bat community composition and habitat-associated niche differentiation in a tropical island ecosystem of Wakatobi, Indonesia - Jimi Purnama Putra S; Lestari Febriant Pitaloka; La Ode Muhammad Erif; Adi Karya (Center for Ecology, Conservation and Ethnobiology Studies, Universitas Sulawesi Barat, 2026)
Bats (Chiroptera) play important ecological roles in tropical island ecosystems, yet information on their community structure in small island systems remains limited. This study aims to analyze species composition, abundance, and habitat associations of bat communities in Wakatobi. Field surveys were conducted in September 2023 across three islands (Wangi-wangi, Kaledupa, and Tomia) using a combination of mist nets and roost observations. A total of 10 sampling points were established, consisting of 5 cave sites, 3 mangrove sites, and 2 terrestrial vegetation sites, with one mist net deployed at each point. Data were analyzed using diversity indices (Shannon-Wiener and Simpson), descriptive abundance analysis, and multivariate approaches including Principal Component Analysis (PCA) and PERMANOVA. A total of 1,604 individuals representing five species from three genera (Pteropus, Rousettus, and Hipposideros) were recorded. The community was strongly dominated by frugivorous bats, particularly Pteropus pumilus (84.47%), which was primarily associated with mangrove and terrestrial vegetation habitats. In contrast, cave habitats were dominated by insectivorous species such as Hipposideros galeritus. Diversity indices indicated low species diversity but high dominance, especially in mangrove habitats. PCA results revealed a clear ecological gradient separating vegetation and cave habitats, with the first two components explaining 100% of total variation (Dim1 = 71.7%; Dim2 = 28.3%). These findings demonstrate strong habitat-driven community structuring and niche differentiation among bat species. This study represents the first assessment of bat community structure in Wakatobi using a PCA-based multivariate approach, providing new insights into habitat–species relationships in small island ecosystems. The results highlight the importance of conserving mangrove and cave habitats as complementary systems supporting bat diversity and ecosystem functions.